2015
DOI: 10.1016/j.bbamem.2015.09.019
|View full text |Cite
|
Sign up to set email alerts
|

The role of endocytosis in the uptake and intracellular trafficking of PepFect14–nucleic acid nanocomplexes via class A scavenger receptors

Abstract: Cell penetrating peptides are efficient tools to deliver various bioactive cargos into cells, but their exact functioning mechanism is still debated. Recently, we showed that a delivery peptide PepFect14 condenses oligonucleotides (ON) into negatively charged nanocomplexes that are taken up by cells via class A scavenger receptors (SR-As). Here we unraveled the uptake mechanism and intracellular trafficking of PF14-ON nanocomplexes in HeLa cells. Macropinocytosis and caveolae-mediated endocytosis are responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…Recently, we showed that PF14-SCO complexes can harness type A SRs to enter the cells (7), which appeared to be a more general cellular uptake mechanism for CPPs and their complexes with NAs (2,(10)(11)(12)(13). Surprisingly, we recently discovered that the particular receptors that are involved in CPP-mediated delivery (SR-A3 and SR-A5) do not localize in the plasma membrane of cells but are recruited there after the exposure to PF14-SCO nanocomplexes (5). In this work we aimed to unravel the mechanisms behind the relocation of SR-As from membranous structures from the cells' cytoplasm to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we showed that PF14-SCO complexes can harness type A SRs to enter the cells (7), which appeared to be a more general cellular uptake mechanism for CPPs and their complexes with NAs (2,(10)(11)(12)(13). Surprisingly, we recently discovered that the particular receptors that are involved in CPP-mediated delivery (SR-A3 and SR-A5) do not localize in the plasma membrane of cells but are recruited there after the exposure to PF14-SCO nanocomplexes (5). In this work we aimed to unravel the mechanisms behind the relocation of SR-As from membranous structures from the cells' cytoplasm to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…PI3Ks are a family of signaling proteins involved in the regulation of multiple cellular processes, among which the regulation of intracellular vesicle trafficking is relevant for our study. PI3Ks also contribute to the macropinosome formation and entry via micropinocytosis, which is also the main uptake mechanism for PF14-SCO nanocomplexes (5). Moreover, PI3K activity and its signaling can be controlled by calcium ions (48,49), which are required for SR-Amediated uptake of PF14-SCO nanocomplexes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations